The Classical Journalism against the New Journalism - Sánchez Vega, Carolina (2015)
The arrival of the New Journalism has certainly changed journalism itself in every single aspect. This new movement seeks to apply narrative resources traditionally assimilated to literature of fiction; thus, creating journalistic texts with stylish and narrative quality enriching News with descriptions, dialogues, opinions and monologues. This article analyzes the characteristics of classic journalism and the New Journalism and as long as this new approach has radically renewed the current journalistic technique.